Investigation of knitted fabric dynamic bagging for textile composite preforms. Issue 4 (2nd April 2016) - El Messiry, Magdi; Mohamed, Abeer
Abstract : Fabric bagging is one of the important phenomena that determine the permanent 3D deformation of fabric under the applied loads. This study focused on dynamical bagging of knitted fabrics and factors affecting it to increase transformation of fabrics preform into various structural shapes through net-shape fabrications. An apparatus for the study of the dynamical bagging was developed. The experimental work shows that the residual bagging depends on the fabric stitch density, fabric areal density, percentage of Lycra. Linear regression equations for the different predictors of fabric bagging were deduced when the fabric is subjected to uniaxial or multi-axial cyclic loading. Although the bagging is considered as a defect for apparel fabrics, it can be used as the formation of the knitted preform for composite structures